EUROPEAN HIGHER EDUCATION AREA DEVELOPMENT: RESULTS AND PROSPECTS - Mospan, N. V. (Continuing Professional Education: Theory and Practice, 2019)
The article says about the current state of development of the European Higher Education Area (EHEA), namely about the analysis of the results of this process after the adoption of the Bologna Declaration and it identifies possible prospects. The study results allow to predict the future direction of development of the EHEA, where the primary can be further expansion of higher education systems